Implementation Of Green Productivity Through Wood Waste Processing To Optimize Productivity And Environmental Performance At PT. Sinar Indah Furniture - Salma, Rizka; Handayani, Wiwik (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research aims to implement the concept of Green Productivity through wood waste processing to optimize productivity and environmental performance at PT Sinar Indah Furniture. In the furniture industry, wood waste is one of the major issues affecting environmental sustainability and production efficiency. The research method used in this study is descriptive analysis with a quantitative approach to evaluate the company’s productivity before and after the implementation of wood waste processing. The results of the study show that the company’s productivity experienced fluctuations during the observation period, but by processing wood waste into economically valuable products, such as particle boards, the company was able to reduce the generated waste and improve productivity. Additionally, the implementation of green productivity has the potential to enhance environmental performance by reducing the negative impact caused by wood waste. This study concludes that the implementation of green productivity not only brings environmental benefits but also increases the company’s economic value. Based on the results, it is recommended to continue the broader implementation of these practices to support the sustainability of the furniture industry in Indonesia